Solving PISA-like Quantity Content: Mathematical Literacy Students Viewed by Level of Mathematical Logic Intelligence - Elyasarikh, Annisa Alvi; Masriyah, Masriyah (Universitas Islam Negeri Sunan Kudus, 2024)
Mathematical literacy related to problem-solving can be measured through PISA or PISA-like, which requires mathematical logic intelligence. Differences in levels of mathematical logical intelligence can result in varying levels of students' mathematical literacy. Therefore, the objective of this study is to describe the mathematical literacy of students based on the level of mathematical logic intelligence when it comes to solving PISA-like problems in quantity content. This study used a descriptive-qualitative approach. Purposive sampling was applied to select three students representing low, medium, and high levels of mathematical logical intelligence. The instruments used were a mathematical logic intelligence test, a PISA-like test, and interview guidance. Data reduction, data display, and making conclusions were data analysis techniques used in this study. The results indicate that a student with high mathematical logical intelligence met all indicators of mathematical literacy. A student with medium mathematical logical intelligence met only the 'formulate' indicator, while a student with low mathematical logical intelligence did not meet any indicators. Teachers can utilize the study's findings to build learning experiences that can improve mathematical literacy of students in solving both PISA and PISA-like problems based on their level of mathematical logic intelligence. Literasi matematis berkaitan dengan pemecahan masalah dapat diukur melalui PISA atau PISA-like yang memerlukan kecerdasan logis matematika untuk menyelesaikannya. Perbedaan tingkat kecerdasan logis matematis memungkinkan perbedaan literasi matematis siswa. Oleh karena itu, tujuan penelitian ini adalah mendeskripsikan literasi matematis siswa berdasarkan tingkat kecerdasan logis matematis dalam menyelesaikan soal PISA-like konten bilangan. Penelitian ini menggunakan pendekatan deskriptif kualitatif. Tiga siswa dipilih secara purposive sampling yakni subjek yang memiliki kecerdasan logis matematis tinggi, sedang, dan rendah. Instrumen yang digunakan adalah tes kecerdasan logis matematis, tes PISA-like, dan pedoman wawancara. Analisis data penelitian ini mencakup reduksi data, penyajian data, dan penarikan kesimpulan. Temuan penelitian menunjukkan bahwa siswa dengan tingkat kecerdasan logis matematis tinggi mampu mencapai semua indikator kemampuan literasi matematis, siswa dengan tingkat kecerdasan logis matematis sedang hanya dapat mencapai kemampuan formulate, sedangkan siswa dengan tingkat kecerdasan logis matematis rendah tidak mampu mencapai semua kemampuan literasi matematis. Guru dapat memanfaatkan temuan penelitian ini sebagai bahan untuk merancang pembelajaran yang dapat meningkatkan literasi matematis siswa dalam memecahkan masalah PISA maupun PISA-like berdasarkan tingkat kecerdasan logis matematis siswa.